WATER AND IONS IN CLAYS: UNRAVELING THE INTERLAYER/MICROPORE EXCHANGE USING MOLECULAR DYNAMICS - Rotenberg B.; Marry V.; Simon C.; Turq P.; Vuilleumier R.; Malikova N. (My University, 2007)
We present the first microscopic description of the exchange of water and ions between clay interlayers and microporosity. A force field based on ab-initio calculations is developed and used in classical molecular dynamics simulations. The latter allow to compute the potential of mean force for the interlayer/micropore exchange for water, Na+ and Cs+ cations and Cl- anions. For the simulated water content (water bilayer, with interlayer spacing 15.4 Å) and salt concentration in the micropore (0.52 mol dm-3) the exchange is found to be almost not activated for water and cations, whereas the entrance of an anion into the interlayer is strongly unfavorable (Δ F ~ 9 kB T). Calculations of the diffusion tensor in the interlayer and in the micropore complete the study of the exchange dynamics. © 2007 Elsevier Ltd. All rights reserved.